Daviault, drunkenness, and discourse: The social construction of the drunkenness defence as a feminist issue. - Frieday, Karen Yvonne. (University of Ottawa (Canada), 1999)
As part of an overall move towards protecting the public (especially those felt to be most vulnerable, e.g. women and children), legislation has recently been tabled which would forbid the use of a defence based on self-induced extreme intoxication producing a state akin to automatism (the drunkenness defence) in trials of general intent offences. This legislation (Bill C-72, s. 33.1), is in direct conflict with the 1994 ruling of the Supreme Court of Canada in Daviault in which the majority found that to deny such a defence in general intent cases was in violation of the principles of fundamental justice enshrined in our Charter of Rights and Freedoms. The Supreme Court of Canada decided that the common-law precedents set by cases such as Beard, Majewski, and Leary, which did not allow evidence of extreme intoxication in general intent cases, had the effect of convicting individuals for crimes in which they were lacking the necessary mens rea or voluntariness. It is proposed that Bill C-72 was tabled in response to feminist claims-making, in addition to the public, and media outcry raised by the Daviault case. (Abstract shortened by UMI.)
Keywords: Sociology, Criminology and Penology.